PENGUKURAN POTENSI NILAI SUMBERDAYA KARAKTERISTIK WISATAWAN WISATA BAHARI DI PULAU CEMARA KECIL TAMAN NASIONAL KARIMUNJAWA - Aditano Yani Retawimbi; Jussac Maulana Masjhoer; Amalia Febryane Adhani Mazaya (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
The waters of Cemara Kecil Island are one of the areas included in the marine tourism utilization zone in the Karimun Jawa National Park (TNKJ) and are locations that are visited by many tourists. Along with the increase in visitors to Cemara Kecil Island, area managers need to prioritize the quality of tours compared to the quantity of tours so that research on tourist characteristics with a focus on analyzing tourists visiting Cemara Kecil Island is important to do. The purpose of this study was to determine the characteristics of marine tourism tourists on Cemara Kecil Island. The research was conducted on Pulau Cemara Kecil, TNKJ. Primary data consists of interview data of respondents with a total of 51 respondents. The results show that most of the tourists who come are female (53%) with the largest age range being between 21-30 years (57%), the education level is dominated by Strata-1 (51%) with the most income being around Rp. 3,000,000 – Rp. 4,000,000 (37%). Travel time for tourists from the distance of origin to KNP is mostly in the range of 12-24 hours (61%). The distance from tourists to tourist sites is mostly in the range of 200-500 km (39%). Based on these results, several management steps that can be taken are through increasing the promotion of Cemara Kecil Island tourism and meeting the needs of tourists according to the characteristics of marine tourism tourists on Cemara Kecil Island.